Kindergarten Cop: A Case Study of How a Coalition Between School Districts and Law Enforcement Led to School Resource Officers in Elementary Schools. (June 2021) - Viano, Samantha; Curran, F. Chris; Fisher, Benjamin W.
Adopting school resource officers (SROs) is a popular response to school shootings. Using the advocacy coalition and multiple streams frameworks, we explore how school districts in one county formed a coalition with the Sheriff's Department, adopting SROs in elementary schools following the Sandy Hook shooting. We describe how this coalition was bound together by shared beliefs on school safety and the goodness of law enforcement. The implementation activities of SROs related to the beliefs of the coalition, focusing on security and relationship building. The beliefs were not uniformly understood by SROs—many interpreted their role to include student discipline and managing behavior of students with disabilities. The findings show the utility of comparing policy adoption processes with implementation activities.